2021
DOI: 10.1111/cid.13051
|View full text |Cite
|
Sign up to set email alerts
|

Buccal bone dimensional changes at immediate implant sites in the maxillary esthetic zone within a 4–12‐month follow‐up period: A systematic review and meta‐analysis

Abstract: Objective: To evaluate the changes in buccal bone dimensions (CBD) following immediate implant placement in the maxillary esthetic zone and to identify the factors influencing the degree of buccal bone resorption for different placement and restoration protocols.Material and methods: An electronic search was conducted using the EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), and MEDLINE (PubMed) databases, combined with a manual and gray literature search, up to January 2021.Selected clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…47 Nevertheless, a plethora of studies using this methodologic assessment are available in the literature. 15,29,30,[32][33][34]37,38,42,48 In the current study, an implant template with the same dimensions of the implant was aligned in the imaging software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Nevertheless, a plethora of studies using this methodologic assessment are available in the literature. 15,29,30,[32][33][34]37,38,42,48 In the current study, an implant template with the same dimensions of the implant was aligned in the imaging software.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses of the buccal bone thickness on CBCT reconstructions also have some limitations due to image artifacts produced by the implant 47 . Nevertheless, a plethora of studies using this methodologic assessment are available in the literature 15,29,30,32–34,37,38,42,48 . In the current study, an implant template with the same dimensions of the implant was aligned in the imaging software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different HTA techniques, such as gap filling, over‐contour augmentation, or socket shield technique, were not further analysed in this study. Another systematic review reported that gap filling showed 0.58 mm BBT reduction, while over‐contour augmentation showed 0.80 mm BBT reduction, without significant difference (Mao et al, 2021). However, the choice of HTA techniques was mainly based on the presence of an initial buccal bone defect, which was different among studies.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, compromised post-extraction sockets have showed successful immediate implant placement when combined with soft tissue and bone grafting. 11,12…”
Section: Post-extraction Socket Typementioning
confidence: 99%